An alternative transformation in ranking using l1-norm in data envelopment analysis - S. Ziari (Journal of Industrial Engineering International, 2016)
Jahanshahloo et al. (Appl Math Comput 153:215-224, 2004) propose a method for ranking extremely efficient decision making units (DMUs) in data envelopment analysis (DEA) using super-efficiency technique and l1-norm and they show that the presented method is able to eliminate the existing difficulties in some methods. This paper suggests an alternative transformation to convert the nonlinear model proposed by Jahanshahloo et al. (Appl Math Comput 153:215-224, 2004) into a linear programming form. The present paper shows that model with this transformation is equivalent to the above-mentioned nonlinear model. The motivation of this work is to linearize the proposed nonlinear model by Jahanshahloo et al. (Appl Math Comput 153:215-224, 2004) which has the higher order of complexity.
Keywords: 650; Data envelopment analysis (DEA); Ranking; Efficiency; Extremely efficient; Chinese cities